2019
DOI: 10.5194/amt-12-1219-2019
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the differential freezing nucleus spectra derived from drop-freezing experiments: methods of calculation, applications, and confidence limits

Abstract: Abstract. The differential nucleus concentration defined in Vali (1971) is re-examined and methods are given for its application. The purpose of this document is to facilitate the use of differential spectra in describing the results of drop freezing, or similar, experiments and to thereby provide additional insights into the significance of the measurements. The additive nature of differential concentrations is used to show how the background contribution can be accounted for in the measurements. A method is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 20 publications
1
79
0
Order By: Relevance
“…6). This photobleaching process has also been experimentally characterized for aerosol probe molecules (Zhao et al, 2015), for biomass burning aerosols (Wong et al, 2017) and for α-pinene secondary organic aerosols (Walhout et al, 2019). We show here that photobleaching is concurrent with a gain in CCN, a loss in IN activity and a loss in organic carbon.…”
Section: Absorbance and Photobleachingsupporting
confidence: 61%
“…6). This photobleaching process has also been experimentally characterized for aerosol probe molecules (Zhao et al, 2015), for biomass burning aerosols (Wong et al, 2017) and for α-pinene secondary organic aerosols (Walhout et al, 2019). We show here that photobleaching is concurrent with a gain in CCN, a loss in IN activity and a loss in organic carbon.…”
Section: Absorbance and Photobleachingsupporting
confidence: 61%
“…Drop freezing assays investigate heterogeneous ice nucleation in an array of droplets of microlitre volumes and are able to detect low concentrations of INPs. Droplet freezing experiments were first reported by Vali and Stansbury (1966) and have since then been used in numerous studies (e.g. Stopelli et al, 2014;Hill et al, 2014;Hiranuma et al, 2015b;Tobo, 2016).…”
Section: Freezing Experiments Performed With Drinczmentioning
confidence: 99%
“…DRINCZ is based on the design of Stopelli et al (2014) and Hill et al (2014), which was initially suggested by Vali and Upper (1995). It consists of a temperature-controlled ethanol bath (LAUDA Proline RP 845, Lauda-Königshofen, Germany), a home-built LED light consisting of several LED light strips enclosed in an ethanol-proof housing, a homebuilt 96-well tray holder and camera mount, a webcam (Microsoft LifeCam HD-3000), and a custom-designed bath leveler, composed of a bath level sensor and valve (see Sect.…”
Section: Instrument Designmentioning
confidence: 99%